ROLE OF THE CULTURAL CONTEXT IN DETERMINING THE USE OF PATIENT SAFETY; A MIX METHOD STUDY: Cultural Context Role in Patient Safety - Saqib Khan, Najm Us; Hafeez, Assad; Khadim, Rehana; Haider, Anam; Hisam, Aliya; Butt, Tahir Mahmood (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the role of the cultural context in determining the use of patient safety by participants from private and public sector hospitals of Karachi, Pakistan.Study Design: Mix method study.Place and Duration of Study: In two tertiary care hospitals (one private and one public sector) of Karachi from Nov 2016 till Nov 2017.Methodology: A sample size of 153 was enrolled by consecutive convenient sampling technique. The role of the cultural context of both hospitals was compared by asking questions from the hospital's staff. Data were collected by the researcher using an open and closed-ended questionnaire.Results: Data of 153 successful and filled questionnaires were analyzed. Out of 153, 78 (51%) cases were for private hospitals and 75 (49%) cases were for public hospitals. The role of the cultural context in determining the use of the patient safety concept was not sufficiently understood by participants of both hospitals, and most of the participants gave vague answers.Conclusion: Cultural context is one of the key factors in patient safety as with collective mindfulness about safety issues, and health care can be delivered safely.